The effect of metformin and P38 MAPK inhibitor on diabetic bone porosity in non-obese type 2 diabetic rats - Punyanuch Adulyaritthikul (2020)
© 2019 Punyanuch Adulyaritthikul et al. Hyperglycemia enhances bone resorption and impairment. Controlling blood glucose via metformin benefits bone cells. Hyperglycemia enhances basal phosphorylation of p38 mitogen-activated protein kinase (MAPK), which aggravates bone resorption. Therefore, the aim of this study was to assess the osteoprotective effects of metformin and p38 MAPK inhibitor in non-obese T2DM rats. In this study, non-obese T2DM (Goto-kakizaki, GK) rats were divided into four groups, including DM group, metformin treatment, SB203580 treatment, and metformin combined with SB203580. Wistar rats were used as control group. Femur, tibia, and iliac rat bones were collected to determine bone porosity via synchrotron radiation microtomography. Primary osteoblasts were isolated from calvaria to investigate cell proliferation and osteoblast function, including alkaline phosphatase (ALP) expression and calcium deposition. The results showed that diabetes increase bone porosity. Treatment with metformin significantly reduced porosity in trabecular and cortical bone of the femur, tibia, and iliac, while SB203580 significantly reduced porosity in cortical bone. A combination group showed significantly reduced bone porosity only in trabecular bone of the femur. Isolated osteoblasts showed lower growth rates. Treatment with metformin significantly increased cell proliferation, ALP expression, and calcium deposition. In summary, metformin treatment improved bone quality by reducing bone porosity, increasing cell proliferation, and improving osteoblast characteristics.